Determination of Optical Constants and Thickness of Nanostructured ZnO Film by Spin Coating Technique - Ghimire, R. R.; Dahal, Y. P.; Rai, K. B.; Gupta, S. P. (Journal of Nepal Physical Society, 2021)
In this report, we have investigated optical constants and thickness of nanostructured ZnO films grown on a glass substrate by sol-gel spin coating technique using zinc acetate as precursor. Optical constants such as complex refractive index ñ and dielectric constant ϵ determined from the transmittance spectrum in the ultraviolet, visible, near infrared (UV-VIS, NIR) region by envelope method. The value of refractive index decreases from 2.34 to 1.86 and extinction coefficient increases from 0.28 to 0.64 with increasing wavelength. The decreasing behavior of refractive index is attributed due to the increase in transmission and decrease in absorption coefficient with increasing wavelength. The film exhibits reasonably high transmittance (>80%) in the visible region. Absorbance coefficient α and film thickness (d) were calculated from the interference of fringes of transmittance spectrum. The band gap and thickness of the film were found 3.02 eV and 275nm, respectively. The thickness of the film measured by envelope method is validated with cross-section micrograph of SEM images which is about 285 nm. The real part of the dielectric function of nanostructured ZnO decreases with increasing wavelength where as the imaginary part of dielectric constant increases with increasing wavelength. The observed high value of refractive index n and real part of dielectric constant ϵ at lower wavelength is due to band edge absorption of carriers. The dispersion relation shows the increase of complex refractive index and dielectric constant at the high frequency regime is due to the discharging of defect levels using optical excitation of carriers in the visible region.